Pemahaman tentang Riba dan Teknologi Finansial Penyebab Berkurangnya Pegawai Bank Konvensional - Aries Kurniawan; Nanang Bagus Setiawan (Entrepreneurship Faculty, Universitas Garut, 2020)
Abstract– This study aims to determine the reasons for the reduction in the number of conventional bank employees. Some data collected by researchers of several banks that experienced a decline were PT Bank Danamon Indonesia Tbk. Especially for bank employees only in 2017 the number of Danamon employees in 2017 reached 16,811 people this number decreased by 6,021 when compared to 2016 with a number of 22,832. This number shows a decrease of 4,391 people when compared to 2015 with a total of 27,223.The same thing was experienced by PT Bank Mandiri Tbk (Bank Mandiri). This red plate bank also experienced a decrease in the number of employees. Based on financial reports published annually, Bank Mandiri employees number 38,307 people, a decrease of 633 people compared to the 2016 period of 38,940. Likewise, BNI (Bank Negara Indonesia) which has 27,209 employees decreased by 975 compared to 2016 with 28,184 employees. Maybank also has fewer employees. In 2017, based on financial statements without audits the number of employees reached 6,727 people, a decrease of 181 compared to 2016 of 6,908. This number is down 513 people compared to the previous year with a total of 7,421 employees. This study uses qualitative research methods, namely in-depth interview data collection with former employees and active banking employees. The researcher also conducted focus group discussions / FGD (Forum Group Discussion) between active bank employees and former banking employees who had resigned.As a result, there are two main factors that cause the reduction in the number of conventional bank employees in Indonesia. First, physical factors, namely technological advances in the industrial era 4.0. The second psychological psychological factor, namely the increase in knowledge and confidence of bank employees on the prohibition of usury based on Islamic teachings. Abstrak- Penelitian ini bertujuan untuk mengetahui alasan berkurangnya jumlah karyawan bank konvensional. Beberapa data yang dihimpun peneliti beberapa bank yang mengalami penurunan adalah PT Bank Danamon Indonesia Tbk. Khusus untuk karyawan bank saja pada tahun 2017 jumlah karyawan Danamon tahun 2017 mencapai 16.811 orang jumlah ini menurun 6.021 saat dibandingkan tahun 2016 dengan jumlah 22.832. Jumlah ini menunjukkan turun 4.391 orang saat dibandingkan tahun 2015 dengan jumlah 27.223. Hal yang sama juga dialami oleh PT Bank Mandiri Tbk (Bank Mandiri). Bank plat merah ini juga mengalami penurunan jumlah pegawai. Berdasarkan laporan keuangan yang terbit setiap tahun, pegawai Bank Mandiri berjumlah 38.307 orang, menurun 633 orang dibandingkan periode 2016 yang berjumlah 38.940. Demikian juga untuk BNI (Bank Negara Indonesia) yang mempunyai karyawan 27.209 menurun 975 dibandingkan tahun 2016 dengan jumlah karyawan 28.184. Maybank juga berkurang pegawainya. Tahun 2017, berdasar laporan keuangan tanpa audit jumlah karyawan mencapai 6.727 orang mengalami penurunan 181 dibanding tahun 2016 sebanyak 6.908. Jumlah ini turun 513 orang dibanding tahun sebelumnya dengan jumlah 7.421 karyawan. Penelitian ini menggunakan metode penelitian kualitatif yaitu pengumpulan data wawancara mendalam dengan para mantan pegawai dan pegawai aktif perbankan. Peneliti juga melakukan diskusi kelompok terarah / FGD (Forum Group Discussion) diantara pegawai bank yang aktif dan mantan pegawai perbankan yang telah mengundurkan diri. Hasilnya, terdapat dua faktor utama yang menyebabkan berkurangnya jumlah karyawan bank konvensional di Indonesia. Pertama, faktor fisik yakni kemajuan teknologi pada era industri 4.0. Kedua faktor psikologis emosional, yakni meningkatnya pengetahuan dan keyakinan karyawan bank atas haramnya riba berdasarkan ajaran Islam.